Courant D'Air (1997)
Biblioteca Departamental de Pret, Guadalupe. Por Valérie Vaudou y Laurence Allegret
Keywords: BIBLIOTECAS; BIBLIOTECAS PUBLICAS; FRANCIA; ARQUITECTURA BIOCLIMATICA; VAUDOU, VALÉRIE; ALLÉGRET, LAURENCE